Magnetizability of doublet radicals using fock space multi-reference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2009)
In this article, we report the first implementation of the recently developed Fock space multi reference Coupled cluster (FSMRCC) response approach for magnetizabilities. The FSM-RCC treats dynamic and static correlation in a very extensive manner. We report pilot application of the diarnagnetizability of NO, NO2, OH, and BH2 radicals. We also report preliminary applications of the paramagnetic magnetizability of the NO radical. Standard atom-centered Gaussian basis functions have been used, and this allowed US to Study the gauge dependence of the magnetizabilities. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 109: 2191-2198, 2009
Keywords: Fock space; magnetizability; multireference

Chemical shielding of closed-shell molecules using extended coupled-cluster theory - Ravichandran, Lalitha; Joshi, Sayali; Vaval, Nayana (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In this paper we report calculation of the nuclear magnetic shielding constant using extended coupled cluster response approach. We present the results for the HF, BH, CO and N(2) molecules. These results show importance of correlation corrections for the shielding constant.
International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, Indian Inst Astrophys, Kodaikanal Observatory, Bangalore, INDIA, JAN 28-31, 2009

Effect of triples to dipole moments in fock-space multireference coupled cluster method - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2011)
In this paper, we present the new implementation of partial triples for the dipole moment of doublet radicals in Lagrangian formulation of Fock-space multireference coupled cluster (A-FSMRCC) response method. We have implemented a specific scheme of noniterative triples, in addition to singles and doubles schemes, which accounts for the effects appearing at least at the third order in dipole moments. The method is applied to the ground states of OH, OOH, HCOO, CN, CH, and PO radicals.

Fock-space multi-reference coupled-cluster response with the effect of triples on dipole moment of ClO and SF radicals - Ravichandran, Lalitha; Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2012)

Partial triples excitation to the fock space multi-reference singles and doubles: dipole moment of doublet radicals - Ravichandran, Lalitha; Vaval, Nayana; Pal, Sourav (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
We present the partial triples effect on the dipole moment of doublet radicals in Lagrangian formulation of Fockspace multi-reference coupled cluster response method(A FSMRCC). This specific scheme uses non-iterative triples, in addition to singles and doubles excitations(A FSMRCCSD(T*)), which accounts for the effects appearing at least at the third order in dipole moment. This method is applied to the ground states of small radicals.
International Conference of Computational Methods in Sciences and Engineering (ICCMSE), Kos, GREECE, OCT 03-08, 2010
Keywords: Dipole moment; Multi-reference; Triples